The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1155/2022/7807956
|View full text |Cite|
|
Sign up to set email alerts
|

Low Expression of miR-491-3p Is Correlated with Lymph Node Metastasis in Gastric Cancer

Abstract: Objective. MiR-491-3p, as a tumor suppressor miRNA, was found decreased in many solid tissues. In this study, we aim to investigate miR-491-3p expression in gastric cancer with or without lymph node metastasis (LNM). Methods. GSE173215 dataset from Gene Expression Omnibus (GEO) was used to measure miRNA expression from tissue samples of gastric cancer patients. Moreover, gastric tumor tissues (non-LNM: n = 78; LNM: n = 68) were obtained to detect the miR-491-3p expression. Receiver operating characteristic (RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…LNM in GC is a complex and orderly process, involving the acquisition of invasive phenotype at the primary tumor site, preparation of metastasis channels, regulation of immune microenvironment, preparation of microenvironment at the metastasis site, and other pathological processes [5][6][7][8]. In-depth exploration and study of the pathological mechanism in the process of LNM would better understand the biological behavior of GC and provide more targets for the diagnosis and treatment [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…LNM in GC is a complex and orderly process, involving the acquisition of invasive phenotype at the primary tumor site, preparation of metastasis channels, regulation of immune microenvironment, preparation of microenvironment at the metastasis site, and other pathological processes [5][6][7][8]. In-depth exploration and study of the pathological mechanism in the process of LNM would better understand the biological behavior of GC and provide more targets for the diagnosis and treatment [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…MiR-491-3p is one of the mature products of miR-491. Recently, miR-491-3p has been reported to be involved in the progression of several cancers, such as retinoblastoma, tongue cancer, glioblastoma, and gastric cancer ( Hu et al, 2021 ; Zheng et al, 2015 ; Li et al, 2015 ; Yu & Luo, 2022 ). Furthermore, it has been demonstrated that miR-491 facilitates CRC cell apoptosis by reducing Bcl-XL expression ( Nakano et al., 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%